(untitled) (Journal of Global Humanities and Social Sciences, 2025)
In the context of the booming development of new media and digital technology, the way of information dissemination, the mode of learning and the means of education have undergone a radical change. However, this change has challenged the traditional teaching methods of Chinese Language and Literature and given it unprecedented development opportunities. With the wide application of new media technologies and the increasing abundance of digital resources, how to effectively integrate these emerging technologies and resources into the teaching of Chinese Language and Literature has become a problem that needs to be solved for the education reform. In this context, this paper discusses the reconstruction of the teaching mode of Chinese language and literature under the dual drive of new media and digital technology, aiming to improve the quality of teaching through innovative teaching methods, optimizing teaching content, and at the same time strengthening the construction of the teaching team and teaching facilities, so as to provide a strong support for the modernization and internationalization transformation of the education of Chinese language and literature, and to push it to realize the leapfrog development under the background of the new era.